Method and apparatus for quantum-mechanically generating a random number - , Suryadi; Mohd Zain, Norzaliman; Wahiddin, Mohamed Ridza (2010)
A method (100) and apparatus (200) for quantum-mechanically generating a random number based on polarization states of spontaneous parametric down- converted photons. The method (100) and apparatus (200) comprises a photon source (202) to generate a beam of photons (102), a first type-l nonlinear crystal (206) and a type-l second nonlinear crystal (207) to down-convert the beam of photons through spontaneous parametric down conversions to generate a pair of unidirectional beam of photons with random polarization states (104), characterized in that the first type-l nonlinear crystal (206) is adjacent to the second type-l nonlinear crystal (207) and optical axis of the first type-l nonlinear crystal (206) is orthogonal to optical axis of the second type-l nonlinear crystal (208), a polarized beam splitter (210) to split the pair of unidirectional beam of photons based on polarization states of the pair of unidirectional beam of photons into a beam of horizontally polarized photons and a beam of vertically polarized photons (106), a first detector (212) and a second detector (214) to detect the presence of the beam of horizontally polarized photons and the beam of vertically polarized photons respectively (108), and an electronic logic (216) to assign a first value to every photon in the beam of horizontally polarized photons and assign a second value to every photon in the beam of vertically polarized photons to generate a random number (110).